2019
DOI: 10.1371/journal.pone.0222675
|View full text |Cite
|
Sign up to set email alerts
|

A ten-year review of ESBL and non-ESBL Escherichia coli bloodstream infections among children at a tertiary referral hospital in South Africa

Abstract: IntroductionThere are few studies describing Escherichia coli (E. coli) bloodstream infection (BSI) among children in Africa, yet E.coli is increasing in importance as a cause of antibiotic resistant infection in paediatric settings.MethodsIn this retrospective, descriptive study aspects of E. coli BSI epidemiology are described over a 10-year period including incidence risk, risk factors for extended-spectrum β-lactamase (ESBL)-producing E. coli BSI, antibiotic susceptibility of the bacterial isolates and out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 21 publications
(29 reference statements)
1
16
0
Order By: Relevance
“…However, the risk factor analysis showed that hospitalisation for more than 7 days before enrolment was an independent risk factor for ESBL-PE colonisation. This finding strongly suggests that the healthcare environment is an important site of colonisation and is consistent with previous BSI studies that showed that 95% and 55% of K. pneumoniae and E. coli BSIs respectively are hospital-acquired or healthcare-associated [41,42].…”
Section: Plos Onesupporting
confidence: 92%
See 2 more Smart Citations
“…However, the risk factor analysis showed that hospitalisation for more than 7 days before enrolment was an independent risk factor for ESBL-PE colonisation. This finding strongly suggests that the healthcare environment is an important site of colonisation and is consistent with previous BSI studies that showed that 95% and 55% of K. pneumoniae and E. coli BSIs respectively are hospital-acquired or healthcare-associated [41,42].…”
Section: Plos Onesupporting
confidence: 92%
“…invasive infection [44,51]. Furthermore, of K. pneumoniae and E. coli isolates causing BSI at RCWMCH, 83% and 30% are ESBL-PE, respectively [41,42]. This study was not designed to determine the timing of colonisation of ESBL-PE and CRE and hence we were unable to establish the extent of community versus hospital acquisition.…”
Section: Plos Onementioning
confidence: 97%
See 1 more Smart Citation
“…. The presence of this enzyme is a universal problem and occurs mainly due to the indiscriminate use of broad-spectrum cephalosporins in the hospital environment [Malande et al, 2019;Brixner et al, 2019].…”
Section: Discussionmentioning
confidence: 99%
“…ESBL-producing bacteria, including E. coli are frequently resistant to multiple antimicrobials including 3rd and 4th generation cephalosporins in addition to quinolones and aminoglycosides [1,2,4]. These bacteria have been designated priority group 1 pathogens for the development of alternative antimicrobial therapies by the World Health Organization [5] as they can cause serious urinary tract [6,7] and bloodstream [8][9][10] infections, occasionally resulting in mortalities [11].…”
Section: Introductionmentioning
confidence: 99%